Right colon volvulus: about 3 observations - Aliano, Omar; Soto, Juan; Nusspaumer, Federico; Goller, Wolfgang (Cirugía del Uruguay, 1974)
In describing a series of three cases of right colonic volvulus, authors outlines main clinical elements with stress of early diagnosis and on the enormous importance of ray studies. Toe varios types of right colonic volvulus are described and classified with description of therapy for such cases.